Penerapan Pidana Mati Terhadap Pengedar Narkotika Sebagai Instrumen Kebijakan Hukum Pidana Dalam Pemberantasan Narkotika Di Indonesia - Putri Ayu Amanda; Henny Yuningsih; Irsan Irsan (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The imposition of the death penalty on drug dealers in Indonesia remains a key instrument of criminal law policy in the eradication of narcotics. However, its implementation has generated considerable debate regarding its effectiveness, legal certainty, and human rights protection. This study aims to analyze the implementation of the death penalty in Indonesia, identify obstacles to its implementation for drug offenders, and examine efforts to make the execution of the death penalty more efficient in the future. This study employed a normative legal research method with legislative, conceptual, case-based, and futuristic approaches. The legal materials used consisted of primary, secondary, and tertiary legal materials, analyzed descriptively and qualitatively. The results indicate that the death penalty is still regulated in Indonesian positive law, particularly in the Narcotics Law and the New Criminal Code. However, its implementation faces obstacles such as uncertainty regarding executions, lengthy legal processes, and human rights considerations. Therefore, clearer regulations and more effective policies are needed to ensure the implementation of the death penalty provides legal certainty and supports drug eradication efforts in Indonesia.